UJI KEEFEKTIFAN PERENDAMAN BENIH DAN PEMBERIAN KOMPOS PANGKASAN MUCUNA TERHADAP PERTUMBUHAN Mucuna bracteata - Mazidah Ulfa; Toga Simanungkalit; Irsal Irsal (Jurnal Agroekoteknologi, 2014)
ABSTRACTThe efectivity of soaking seed with compot residu of mucuna on growth Mucuna bracteata. Thisstudy aims to evaluate efectivity of soaking seed with compost residu of Mucuna on growthMucuna bracteata . The research was conducted at the Tumpatan Nibung, kecamatan batang kuis,kabupaten Deli Serdang. Using the randomized block design with two factors that isand compost residu of Mucuna (1:1, 1:2,1:3) with 3 replications. Observation variable is shoot capacity, growth percentation, number ofbranch, total leaf area, wet weight of the top stem, an dry weight of the top stem. The result showedthat soaking seed is significant to shoot capacity, number of branch and wet weight of the top stembut not significant to total leaf area, growth perecentation and dry weight if the top stem. Compostresidu of Mucuna is significant to number of branch, total leaf area, and wet weight of the top stembut not significant to shoot capacity, growth percentation, and dry weight of the top stem. Treatmentinteraction is not significant to all observation bariable.Key words: soaking seed, compost residu of Mucuna, Mucuna bracteata